REDISCOVERING LIFE (POST TRAUMATIC GROWTH ON PEOPLE LIVING WITH HIV) - Niken Wulan Hasthi Murti; Sri Puguh Kristiyawati; Ismonah Ismonah (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Post-traumatic growth is a life change. People living with HIV who start to adapt to the current condition have a better life and positive emotion by rediscovering happiness. Post-traumatic growth occurs due to individual thoughts regarding life purposes and reviewing their life priorities. Objectives: This study aimed to explore the post-traumatic growth process experienced by people living with HIV. Methods: This study employed the qualitative study method with a descriptive phenomenology approach on six participants with HIV at Yayasan Sehat Peduli Kasih, Semarang. The participants were selected following the inclusion criteria, i.e., 24-25-year-olds with no cognitive disorders and regular treatments. The exclusion criteria in this study were participants who could not attend the interview process, although the researchers already made recurring appointments. The interview type utilized in this study was a semi-structured interview. The data analysis model in this study followed the data analysis steps of the colaizzi method. Results: Four themes emerged as part of post-traumatic growth. The four identified themes in this study are 1) early stage of HIV positive, 2) post-traumatic growth process, 3) becoming a better person after rediscovering life, and 4) future wishes after rediscovering life. The acquired themes are illustrations of post-traumatic growth in rediscovering life. Conclusion: Most People living with HIV have rediscovered purposes and wishes, although they continue to eliminate self-stigma and transform self-image to be positive. It is necessary to develop an HIV intervention program to improve and help the sufferers encounter internal stigma. The interventions include any ECT and spiritual mindfulness that focus on improving self-confidence.